Dampak Kebijakan Pajak Penghasilan PPH 21 Terhadap Beban Pajak Karyawan Di Perusahaan Umum Daerah Perkebunan Kahyangan Jember - Dean Vandika; Rofiqurrahman Rofiqurrahman (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the impact of Income Tax Article 21 (ITA 21) policy on employees' tax burden and its implications for Corporate Income Tax (CIT) at the Regional Public Company (Perumda) Kahyangan Jember Plantation. Currently, the company applies the Net Method, where the company bears the entire PPh 21 of employees. Consequently, the tax paid cannot be deducted from the taxable income in the fiscal financial statements, which causes a higher Corporate Income Tax expense. Therefore, this study evaluates the effectiveness of the Gross Up method compared to the Net method in optimizing the company's tax efficiency. This research uses a descriptive analytical method with a case study approach, where data is obtained from the company's financial statements, employee payroll, and interviews with related parties. The analysis is conducted by comparing three methods of calculating Income Tax 21, namely Gross Method, Net Method, and Gross Up Method, to assess their impact on corporate income tax expense and company net profit. The results showed that the application of the Gross Up Method provides greater benefits than other methods. With this method, the company can significantly reduce the corporate income tax expense, increase net profit after tax, and still maintain employee take-home pay. In addition, the Gross Up Method ensures compliance with tax regulations without reducing employee welfare. Therefore, this method is recommended as a more efficient tax planning strategy for Perumda Perkebunan Kahyangan Jember to optimize profitability and tax efficiency.